A Case of Juvenile and Adenomatous Polyposis Associated with Telangiectasia and Colonic Carcinoma - Z. MUNGAN,; N. EROL,; G. BOZTAŞ,; C. ULAŞOĞLU,; O. ÇUBUKCU,; R. ERDOĞAN,; R. SEZER, (Turkish Journal of Gastroenterology, 2020)
-